Organizational citizenship behavior as a predictor of student academic achievement - Khalid, Shaiful Annuar; Jusoff, Kamaruzaman; Othman, Mahmod; Ismail, Mohammad; Abdul Rahman, Norshimah (Canadian Center of Science and Education, 2010)
This study employed social exchange theory to examine the connection between one of the elements of teaching strategies, that is, lecturers’ organizational citizenship behavior (OCB) and students’ academic achievement. Student needs for achievement was used as moderator. Analysis was conducted on a survey data of 196 students in one of the local public institutions of higher learning. The results revealed that OCB dimension of altruism and courtesy were significantly related to students’ academic achievement. In addition, conscientiousness positively predicted students’ academic achievement among students with high needs for achievement. These findings indicate that, in order to enhance motivation and learning among students, altruism, courtesy and conscientiousness are some of the important behaviors among lecturers. Interpretations of results, implications and future research are discussed.